Effects of Expectations on Cognitive Enhancement Interventions in Young and Older Adults - Rabipour, Sheida (Université d'Ottawa / University of Ottawa, 2018)
With increasing life expectancy and global population of older adults, preserving cog- nitive function throughout life represents a growing priority. Numerous approaches to cognitive enhancement exist, but few have scientific merit. Among the most preva- lent – and commercialized – approaches are cognitive training (“brain training”) and non-invasive brain stimulation through electric currents applied at the surface of the scalp. The present dissertation describes a collection of work contextualizing the appeal of these cognitive enhancement methods and addressing some of the most pervasive limitations of research in this field thus far. One largely ignored issue in cognitive intervention research pertains to people’s expectations of programs and their relationship with intervention outcomes. In a series of initial studies, we developed and validated the Expectation Assessment Scale (EAS), a tool created to measure as well as prime expectations of outcomes in the context of cognitive enhancement interventions. In our first two studies, we probed expectations of cognitive training or non-invasive brain stimulation in over 1,000 young, middle-aged, and older adults. Ratings on the EAS suggested that older adults may have particularly high expectations of cognitive training, but that expectations can be primed to increase or decrease – at least in hypothetical scenarios. We used these data to assess the psychometric properties of the EAS with item-response theory, and confirmed its internal consistency. Next, we incorporated the EAS into two cognitive enhancement trials, one in- vestigating a computerized cognitive training intervention in nearly 100 older adults and another examining non-invasive brain stimulation in nearly 100 young adults. Both trials had a double-blind balanced-placebo design in which participants were assigned to the intervention or control condition, and then subdivided to receive ei- ther high or low expectation priming (i.e., primed to have high or low expectations of the program’s effectiveness). Although expectation ratings replicated our previous findings, results from these trials suggest little, if any, effect of either expectations or the intervention on performance outcomes. We nevertheless found that participants enjoyed their assigned program and that those who received high expectation prim- ing tended to report a more positive experience. Our findings put into question the effectiveness of such interventions and support the need for more rigorous trials of cognitive enhancement.
Keywords: Expectations; Cognitive enhancement; Brain training; Non-invasive brain stimulation; Placebo effects; Transcranial direct current stimulation (tDCS)